Predestinação e livre arbítrio na teologia de Jacó Armínio : contribuições do arminianismo do século XVI para uma atual tomada de consciência da liberdade humana de julgar e agir com responsabilidade, em uma sociedade em construção - Silva, Germano Soares (2018)
The present work has the purpose of focusing the theological thought of Jacob Arminius on the themes of Free Will and Predestination. These themes have always been discussed by Calvinists on Brazilian soil, and only by the Reformed angle, for the lack of works of Arminius are not known in the theological academies of Brazil. At the beginning of the 21st century, a series of publications about the thinking of Jacob Arminius began, by Brazilian Arminians who struggled and are struggling not to promote meaningless discussions, but to show how Arminius thought and reflected the Sacred Scriptures, producing his messages and his studies to instruct the church where he was pastor in Holland. To the great joy of admirers of the works of Arminius, in 2015, Publishing House Assemblies of God of Brazil (CPAD) published in three volumes the Works of Arminius. This publication served as the basis for the present work, adding other works published by Brazilian and North American Arminian scholars. This work does not deal with all of Arminius's thinking, but it was of personal interest to reflect on Free Will and Predestination. The first chapter deals with the scene of the main controversies and also of the conflicts in the ecclesial reality of the Netherlands from 1609 to 1618. In this scenario were present as main protagonists Calvinists and Arminians. The second chapter deals with the theme of Predestination, not as fatalism, but for adoption and also for the glory of God. Predestination has as its scope the responsibility of the Christian in the Kingdom of God. And finally, the third chapter, which has as its content the meaning of Free Will and its powers to the dimensions of a free and responsible Christendom. It is hoped that all those who are involved in the content of this work will have spirit and action in order to be able to freely reflect on the thought of Jacob Arminius for the existence of a good social and ecclesial reality.